Perancangan Aplikasi Pembelajaran Anatomi Tubuh Manusia Untuk SD Menggunakan Adobe Flash - Ikhwan, Ali; Ardiyansyah, Agung; Maulana, Dimas Krisna; Rayhannur, Muhammad Jaffar; Abdillah, Muhammad Oemar (Jurnal Sains dan Teknologi (JSIT), 2022)
During this digital era, technology has had a huge impact on the way we create, process and enjoy media. The development of multimedia has allowed us to combine various types of media, such as text, images, audio and video, into one interactive and engaging platform. Technology has also made media processing easier and more efficient, allowing us to more quickly and effectively access and enjoy media content. In this article, we will review the development and application of technology in media processing, and discuss how this affects the way we create and enjoy media content. We will also review some case examples that show how technology has changed the multimedia industry and the way we access media content.